PERANCANGAN ULANG TRANSFER CHUTE 63/72 UNTUK MENAIKKAN UMUR LINER, STUDI KASUS DI PT FREEPORT INDONESIA - Ramses Yohannes Hutahaean; Marthina Mini; Rolling Swempry Gaspersz (Geosapta, 2021)
Transfer Chute is one of the important components in the transportation of ore originating from open pit to the stock pile. Damage or leakage in the transfer chute when there is no over haul will result in down time so that it can cause production losses for 10 hours . Damage that often occurs in chute transfers occurs after production increases which causes the conveyor speed to change from 2 m / s to 4 m / s so that the initial design of the transfer chute is not suitable for conveyor speeds to 4 m / s, ore originating from conveyor 63 is not form a rock box on the transfer chute 63/72 but directly hit the liner on the transfer chute.           In this paper presents two material discharge trajectory methods and expain the differences between them, and then we choose a method that approaches the actual condition. From the results of the trajectory analysis, we can determine new dimensions of transfer chute. Based on the modification of the chute transfer, the life time of the liner increased from 4 weeks to 6 months and there was never a "down time" due to an increase in the transfer chute 63/72.